Cornelia de Lange Syndrome and Psychiatric’s Assistance - Katharina Merry Apriliani; Yunias Setiawati (Faculty of Medicine, Universitas Airlangga, 2020)
Cornelia de Lange's syndrome (CdLS) is a genetic disorder characterized by developmental disorders in several organ systems, including the brain, bones, digestion, immunity, endocrine, and others. This syndrome is mainly caused by mutations in the NIPBL, SMC3, and SMC1A genes. CdLS are generally comorbid with developmental or intellectual-level disorders, autism spectrum disorders, self-injury behavior, difficulty speaking, anxiety, hyperactivity, and sleep problems. This CdLS has a significant impact on the quality of life and maladaptive function in patients, as well as causing psychological disorders for families. Therefore, the need for psychiatric assistance for family psychoeducation, psycho-social interventions and cognitive-behavioral education.